PENGARUH HARGA, ULASAN PEMBELI, DAN ONGKOS KIRIM TERHADAP KEPUTUSAN PEMBELIAN MELALUI MARKETPLACE PADA MAHASISWA FISIP UNIVERSITAS RIAU - Risa Sabila; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The passage of an all-instant plot forces us to follow it and are also forced to be able to adapt. Tokopedia and Shopee are the most widely used marketplaceswhen deciding to buy through a marketplace, a customer will definitely consider the things that make him/her confident about buying the product. The product prices listed, features of previous buyer reviews, and shipping costs can be factors to consider before deciding to buy a product. The purpose of this study was to see if there was an effect of price, buyer reviews, and shipping costs on purchasing decisions through the marketplace for physical education students at the University of Riau. This study uses an inferential quantitative method. The population in this study were 5349 faculty of social and political science students at the University of Riau, with a sample of 98 respondents who had shopped at the marketplace obtained using the slovin method. The instrument in this study used a Likert scale of one to five. Methods of data analysis in this study through validity test, reliability test, classical assumption test, and multiple regression test. The results of the study show that prices, buyer reviews, and postage have a partial or simultaneous effect on purchasing decisions through the marketplace for faculty of social and political science students at the University of Riau. The price factor is the dominant factor influencing purchasing decisions through the marketplace for faculty of social and political science students at the University of Riau. Key words: Price, Customer Review, Shipping Cost